Renewable Energy and its Innovative Technologies Proceedings of ICEMIT 2017, Volume 1 - Chattopadhyay, Jayeeta; Singh, Rahul; Prakash, Om (Springer Nature Singapore : Imprint: Springer, 2019)
The book features innovative scientific research by scientists, academicians and students, presented at the International Conference on Energy, Materials and Information Technology, 2017 at Amity University Jharkhand, India. Covering all the promising renewable energies and their related technologies, such as wind, solar and biomass energy, it compiles current important scientific research in this field and addresses how it can be applied in an interdisciplinary manner. The selected conference papers provide important data and parameters for utilizing the main potential renewable energies, and allowing an economic and environmental assessment. The book is a valuable resource for all those who are interested in the physical and technical principles of promising ways to utilize various renewable energies.